Vibration Control of Active Structures An Introduction - Preumont, André; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This textbook is an introduction to the dynamics of active structures and to the feedback control of lightly damped flexible structures; the emphasis is placed on basic issues and simple control strategies that work. Now in its fourth edition, more chapters have been added, and comments and feedback from readers have been taken into account, while at the same time the unique premise of bridging the gap between structure and control has remained. Many examples, covering a broad field of applications from bridges to satellites and telescopes, and problems bring the subject to life and take the audience from theory to practice. The book has 19 chapters dealing with some concepts in structural dynamics; electromagnetic and piezoelectric transducers; piezoelectric beam, plate and truss; passive damping with piezoelectric transducers; collocated versus non-collocated control; active damping with collocated systems; vibration isolation; state space approach; analysis and synthesis in the frequency domain; optimal control; controllability and observability; stability; applications; tendon control of cable structures; active control of deformable mirrors for Adaptive Optics and large earth-based and space telescopes; and semi-active control. The book concludes with an exhaustive bibliography and index. This book is intended for structural engineers who want to acquire some background in vibration control, and for control engineers who are dealing with flexible structures. It can be used as a textbook for a graduate course on vibration control or active structures. A solutions manual is available through the publisher to teachers using this book as a textbook.
oscillator.-   12.4 State transformation.-   12.4.1 Control canonical form.-   12.4.2 Left and right eigenvectors.-   12.4.3 Diagonal form.-   12.5 PBH test.-   12.6 Residues.-   12.7 Example.-   12.8 Sensitivity.-   12.9 Controllability and observability Gramians.-   12.10Internally balanced coordinates.-   12.11Model reduction.-   12.11.1Transfer equivalent realization.-   12.11.2Internally balanced realization.-   12.11.3Example.-  12.12References.-   12.13Problems.-   13 Stability.-   13.1 Introduction.-   13.1.1 Phase portrait.-   13.2 Linear systems.-   13.2.1 Routh-Hurwitz criterion.-   13.3 Lyapunov's direct method.-   13.3.1 Introductory example.-   13.3.2 Stability theorem.-   13.3.3 Asymptotic stability theorem.-   13.3.4 Lasalle's theorem.-   13.3.5 Geometric interpretation.-   13.3.6 Instability theorem.-   13.4 Lyapunov functions for linear systems.-   13.5 Lyapunov's indirect method ..-  13.6 An application to controller design.-  13.7 Energy absorbing controls.-   13.8 References.-   13.9 Problems.-   14 Applications.-   14.1 Digital implementation.-   14.1.1 Sampling, aliasing and prefiltering.-   14.1.2 Zero-order hold, computational delay.-   14.1.3 Quantization.-   14.1.4 Discretization of a continuous controller.-   14.2 Active damping of a truss structure.-   14.2.1 Actuator placement.-   14.2.2 Implementation, experimental results.-   14.3 Active damping generic interface.-   14.3.1 Active damping.-   14.3.2 Experiment.-   14.3.3 Pointing and position control.-   14.4 Active damping of a plate.-   14.4.1 Control design.-   14.5 Active damping of a stiff beam.-   14.5.1 System design.-  14.6 The HAC/LAC strategy.-   14.6.1 Wide-band position control.-   14.6.2 Compensator design.-   14.6.3 Results.-   14.7 Vibroacoustics: Volume displacement sensors.-   14.7.1 QWSIS sensor.-   14.7.2 Discrete array sensor.-   14.7.3 Spatial aliasing.-  14.7.4 Distributed sensor.-   14.8 References.-   14.9 Problems.-   5 Tendon Control of Cable Structures.-   15.1 Introduction.-   15.2 Tendon control of strings and cables.-   15.3 Active damping strategy.-   15.4 Basic Experiment.-   15.5 Linear theory of decentralized active damping.-  15.6 Guyed truss experiment.-   15.7 Micro Precision Interferometer testbed.-   15.8 Free floating truss experiment.-   .
Keywords: Multibody systems; Vibration; Mechanics, Applied; Mechanical engineering; Noise control; Building materials; Multibody Systems and Mechanical Vibrations; Mechanical Engineering; Noise Control; Structural Materials